An alternative process for butanol production: Continuous flash fermentation - Mariano, Adriano Pinto; De Angelis, Dejanira de Franceschi [UNESP]; Maugeri Filho, Francisco; Atala, Daniel Ibraim Pires; Wolf MacIel, Maria Regina; MacIel Filho, Rubens (De Gruyter, 2008)
The objective of this work is to introduce and demonstrate the technical feasibility of the continuous flash fermentation for the production of butanol. The evaluation was carried out through mathematical modeling and computer simulation which is a good approach in such a process development stage. The process consists of three interconnected units, as follows: the fermentor, the cell retention system (tangential microfiltration) and the vacuum flash vessel (responsible for the continuous recovery of butanol from the broth). The efficiency of this process was experimentally validated for the ethanol fermentation, whose main results are also shown. With the proposed design the concentration of butanol in the fermentor was lowered from 11.3 to 7.8 g/l, which represented a significant reduction in the inhibitory effect. As a result, the final concentration of butanol was 28.2 g/l for a broth with 140 g/l of glucose. Solvents productivity and yield were, respectively, 11.7 g/l.h and 33.5 % for a sugar conversion of 95.6 %. Positive aspects about the flash fermentation process are the solvents productivity, the use of concentrated sugar solution and the final butanol concentration. The last two features can be responsible for a meaningful reduction in the distillation costs and result in environmental benefits due to lower quantities of wastewater generated by the process. © 2008 Berkeley Electronic Press. All rights reserved.
Keywords: butanol; flash fermentation; mathematical modeling; simulation; Alternative process; Cell retention systems; Environmental benefits; Ethanol fermentation; Fermentation process; Fermentors; Inhibitory effect; Mathematical modeling; Process development; Sugar conversion; Sugar solutions; Technical feasibility; Acoustic devices; Computer simulation; Distillation; Ethanol; Fermentation; Fermenters; Glucose; Microfiltration; Productivity; Wastewater; Alcohols